Transcriptome Analysis Revealed Highly Expressed Genes Encoding Secondary Metabolite Pathways and Small Cysteine-Rich Proteins in the Sclerotium of Lignosus rhinocerotis - Yap, H.Y.Y.; Chooi, Y.H.; Fung, S.Y.; Ng, S.T.; Tan, C.S.; Tan, N.H. (Public Library of Science, 2015)
Lignosus rhinocerotis (Cooke) Ryvarden (tiger milk mushroom) has long been known for its nutritional and medicinal benefits among the local communities in Southeast Asia. However, the molecular and genetic basis of its medicinal and nutraceutical properties at transcriptional level have not been investigated. In this study, the transcriptome of L. rhinocerotis sclerotium, the part with medicinal value, was analyzed using high-throughput Illumina HiSeqTM platform with good sequencing quality and alignment results. A total of 3,673, 117, and 59,649 events of alternative splicing, novel transcripts, and SNP variation were found to enrich its current genome database. A large number of transcripts were expressed and involved in the processing of gene information and carbohydrate metabolism. A few highly expressed genes encoding the cysteine-rich cerato-platanin, hydrophobins, and sugar-binding lectins were identified and their possible roles in L. rhinocerotis were discussed. Genes encoding enzymes involved in the biosynthesis of glucans, six gene clusters encoding four terpene synthases and one each of non-ribosomal peptide synthetase and polyketide synthase, and 109 transcribed cytochrome P450 sequences were also identified in the transcriptome. The data from this study forms a valuable foundation for future research in the exploitation of this mushroom in pharmacological and industrial applications.